Modified dual tree complex wavelet transform for processing quadrature signals - Serbes, Gorkem; Aydin, Nizamettin (ELSEVIER SCI LTD, 2011)
Dual-tree complex wavelet transform (DTCWT) is a shift invariant transform with limited redundancy. Complex quadrature signals are dual channel signals obtained from the systems employing quadrature demodulation. An example of such signals is quadrature Doppler signal obtained from blood flow analysis systems. Prior to processing Doppler signals using the DTCWT, directional flow signals must be obtained and then two separate DTCWT applied, increasing the computational complexity. In order to decrease computational complexity, a modified DTCWT algorithm is proposed. A comparison between the new transform and the phasing-filter technique is presented. The results show that the proposed method gives the same output as the phasing-filter method and the computational complexity for processing quadrature signals using DTCWT is greatly reduced. (C) 2010 Elsevier Ltd. All rights reserved.
Keywords: Complex wavelets; Wavelet transform; Doppler; Denoising; DOPPLER SIGNALS; Engineering